Effect of different drying methods on total bioactive compounds, phenolic profile, in vitro bioaccessibility of phenolic and HMF formation of persimmon - Kayacan, Selma; Karasu, Salih; Akman, Perihan Kubra; Goktas, Hamza; Doymaz, Ibrahim; Sagdic, Osman (ELSEVIER, 2020)
This study aims to investigate the effects of different drying methods namely, ultrasound-assisted vacuum-drying (USV), freeze-drying (PD), infrared-drying (ID) and hot-air drying (HAD) on bioactive compounds, phenolic profile, in vitro bioaccessibility of phenolic compounds, color change, sugar profile and HMF formation of persimmon fruits. Total phenolic contents (TPC) were 77.2, 112.5, 124.9 and 262.4 mg GAE/100 g for HAD, ID, USV, and FD, respectively. CUPRAC, DPPH, beta-carotene and lycopene level were 219.2-635.2 mg TE/100 g, 101.1-299.7 mg TE/100 g, 294.3-438.5 mg/100 g and 720.6-966.5 mg/100 g, respectively. Drying methods significantly affected both amounts of individual phenolics and their distribution (P < 0.05). Epigallocatechin was determined as a major phenolic compound for all samples (88.2-383.2 mg/100 g). All drying process significantly increased the bioaccessibility of phenolic compounds (P < 0.05). HAD showed the highest In vitro bioaccessibility. All drying methods significantly affected Delta E values (P < 0.05). HMF values were 12.1, 15.0 and 23.4 mg/kg for ID, USV and HAD samples, respectively and was not found for FD. This study suggested that 115V and ID could be used as an alternative drying method to FD and conventional drying due to high drying rate, less phenolic degradation, HMF formation, and color change.
Keywords: Lycopene; beta-carotene; Epigallocatechin; CUPRAC; Flavonoids; ANTIOXIDANT CAPACITY; ORGANIC-ACIDS; ULTRASOUND; QUALITY; FRUIT; KINETICS; STORAGE; FRESH; PHYTOCHEMICALS; POLYPHENOLS; Food Science & Technology